Effect of High-Dose Esomeprazole on CYP1A2, CYP2C19, and CYP3A4 Activities in Humans: Evidence for Substantial and Long-lasting Inhibition of CYP2C19 - Taavi J. K. Kaartinen; Aleksi Tornio; Tuija Tapaninen; Terhi Launiainen; Nina Isoherranen; Mikko Niemi; Janne T. Backman (WILEY, 2022)
In vitro, esomeprazole is a time-dependent inhibitor of CYP2C19. Additionally, racemic omeprazole induces CYP1A2 and omeprazole and its metabolites inhibit CYP3A4in vitro. In this 5-phase study, 10 healthy volunteers ingested 20 mg pantoprazole, 0.5 mg midazolam, and 50 mg caffeine as respective index substrates for CYP2C19, 3A4, and 1A2 before and 1, 25, 49 (pantoprazole only), and 73 hours after an 8-day pretreatment with 80 mg esomeprazole twice daily. The area under the plasma concentration-time curve (AUC) ofR-pantoprazole increased 4.92-fold (90% confidence interval (CI) 3.55-6.82), 2.31-fold (90% CI 1.85-2.88), and 1.33-fold (90% CI 1.06-1.68) at the 1-hour, 25-hour, and 73-hour phases, respectively, consistent with a substantial and persistent inhibition of CYP2C19. The AUC of midazolam increased up to 1.44-fold (90% CI 1.22-1.72) and the paraxanthine/caffeine metabolic ratio up to 1.19-fold (90% CI 1.04-1.36), when the index substrates were taken 1 hour after esomeprazole. Based on the recovery ofR-pantoprazole oral clearance, the turnover half-life of CYP2C19 was estimated to average 53 hours. Pharmacokinetic simulation based on the observed concentrations of esomeprazole and its metabolites as well as their published CYP2C19 inhibitory constants was well in line with the observed changes inR-pantoprazole pharmacokinetics during the course of the study. Extrapolations assuming linear pharmacokinetics of esomeprazole suggested weak to moderate inhibition at 20 and 40 mg twice daily dosing. In conclusion, high-dose esomeprazole can cause strong inhibition of CYP2C19, but only weakly inhibits CYP3A4 and leads to minor induction of CYP1A2. The enzymatic activity of CYP2C19 recovers gradually in similar to 3-4 days after discontinuation of esomeprazole treatment.